Variation and change in future temporal reference with avoir and être - Tristram, Anna (Journal of French language studies, 2021)
Variation and change in the future temporal reference (FTR) sector in French has been the subject of numerous studies, from a variety of perspectives. Most studies consider the patterns of variation and evidence for change by looking at the verbal system as a whole. However, there are indications that some verbs differ significantly in their preference for one or other variant. Avoir and être are two such verbs. This study first examines the overall distribution of the inflected and periphrastic future with these two verbs in the ESLO corpus of spoken French, and considers the evidence for change. A multivariate analysis of the linguistic factors affecting variant selection in FTR with these two verbs reveals no exceptional effects; we thus explore other possible explanations for the exceptional distribution of FTR variants with these two verbs.